TYPOLOGY STUDY OF VERNACULAR COURTYARD-HOUSE IN KERALA, SOUTH INDIA - Indah Widiastuti (Jurnal Sosioteknologi, 2018)
This paper is based on observation about vernacular courtyard-house architecture in Kerala, South India. Traditional architecture in India is generally governed by a knowledge, prescribed in a traditional book. However, from the field observations, we identified many exceptions against the prescribed traditional knowledge. In the case of Kerala, some of the exceptions indicate shared architectural features with indigenous architecture in Indonesian. The analysis uses typology method and unfolds six typologies and three styles of courtyard-houses. They have distinct spatial characters that give importance to women, kitchen, main orientation to water and river, and granary concept.  Makalah ini ditulis berlandaskan hasil observasi lapangan terhadap arsitektur vernakuler rumah courtyard, di Kerala India Selatan. Arsitektur tradisional di India pada umumnya taat pada pengetahuan, yang ditulis dalam sebuah kitab tradisional. Namun, dari pengamatan lapangan, kami mengidentifikasi adanya pengecualian desain dari yang telah diatur dalam buku tradisional tersebut. Dalam kasus arsitektur rumah courtyard Kerala, beberapa pengecualian tersebut justru menunjukkan kesesuaian dengan arsitektur asli di Indonesia. Analisis dilakukan dengan menggunakan metode Tipologi, dan mengungkap enam tipologi serta dua langgam. Pada rumah courtyard Kerala aspek perempuan, dapur, orientasi utama terhadap air dan sungai, serta konsep lumbung mendapat tempat yang penting.